Lempel–Ziv Data Compression on Parallel and Distributed Systems - Sergio De Agostino (Algorithms, 2011)
We present a survey of results concerning Lempel–Ziv data compression on parallel and distributed systems, starting from the theoretical approach to parallel time complexity to conclude with the practical goal of designing distributed algorithms with low communication cost. Storer’s extension for image compression is also discussed.